Comparative in vitro quality evaluation of different brands of Ebastine 10 mg tablets commercially available in Bangladesh - Rahman, Saqib (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.